Clinico-pathological characteristics of colorectal carcinoma at university teaching hospital, Nepal - Shah, Surendra; Shrestha, Samir; Shah, Jay Narayan; Paudyal, Sanjaya (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Colorectal cancer is a major health problem in developing countries. The purpose of this study was to analyze the clinico-pathological characteristics of colorectal carcinoma at Patan hospital, Nepal.Methods: A retrospective chart review was done for patients operated for colorectal carcinoma at Patan Hospital from May 2004 to April 2012. Demographic information, chief complains, site of primary cancer, and histological types were analyzed.Results: There were 73 patients (37 males and 36 females) with colorectal carcinoma. The mean age was 52 years. There were 21 (28.77%) patients below 40 years of age. Patients with rectal carcinoma presented with bleeding per rectum in 69.70% and 60% of patients with colon cancer presented with pain abdomen. Rectum was involved in 31 (42.47%) and right colon in 30 (41.10%). Adenocarcinoma was seen in 72 (98.63%).Conclusions: The colorectal carcinoma is not only the disease of old age. We had 29% of our patients below 40 year. Rectum and right colon were equally affected.